(untitled) (American Journal of Youth and Women Empowerment, 2023)
Women’s rights advocates in Egypt are credited with leading the fight for equal rights for women. They played a vital role in the uprising of women’s rights in parliament and judiciary, and the women of Egypt soared through the Arab Spring revolution after 25th and 30th of January. Women in Arab countries have been marginalized and discriminated, leading to the Arab Spring Revolution of 2010 and 2011, which brought about positive changes for women in their traditional, political and decision-making lives. This study demonstrated every aspect and its outcomes of the revolution started by the women of Arab for their rights. The research is focused on discussing an important topic, namely the role of women in the State’s public policy-making process and ensuring they represent one of society’s most effective forces.